Modelling Green Production Process in the Natural Dyes Batik Industry Using Cleaner Production Options - Siti Ajizah (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
Sustainable production policy has encouraged batik industry to switch synthetic dyes to natural dyes. However, the production process still brings negative impacts on the environment as well as on humans. In order to solve this problem, the batik industry needs to develop green production model using cleaner production options. The purpose of this research is to design green production model for greening the natural dyes batik industry. The research was conducted in the natural dyes batik industry “Mbah Guru”. Mbah Guru batik industry is located in Lamongan, East Java. The research used a feasibility study by using Pay Back Period (PBP). The last decision making of cleaner production options was used Bayes Method to assess and determine cleaner production options based on technical, economical, and environmental aspects. The result showed that all of cleaner production options are feasible.